Atuação de profissionais na atenção primária à saúde em fronteira internacional: vivências, desafios e possibilidades - Conde, Olga Lucía Mosquera (2024)
Objective: to understand how professionals work in PHC at the International Border, considering their experience, challenges and possibilities. Method: this is a research with a qualitative approach, of an exploratory nature, outlined by the theoretical and methodological framework of Alfred Schütz's Social Phenomenology. It will be developed within the scope of the Primary Health Care (PHC) network of the municipality of Foz do Iguaçu PR. The research participants will be PHC professionals, Nurses, Doctors, Nursing Technicians and Community Health Agents (ACS). Data collection will be carried out through a questionnaire to identify the socioprofessional profile of the participants and a phenomenological interview with a semi-structured script, containing nine guiding questions that allowed to know the "Reasons why", what has already been experienced by professionals and the "Reasons for", the expectations of these participants. Results: Eight concrete categories of experience were identified, six of which referred to the “Reasons Why”: Understanding of Primary Health Care (PHC); Knowledge about Health and Borders; Working in APS at the International Border; Perception of the population served in PHC at the border; Positive points in working in Border PHC and Challenges faced. Two categories refer to “Reasons for”: and What do you expect as a Border PHC professional and Expectations for PHC at the border. Conclusions: The reports revealed that health professionals identify the border as a challenging territory, with intense relationships capable of providing a wealth of health knowledge through multicultural interaction. The performance is characterized by multicultural care, diversity, as well as high demands, deficient human resources, work overload and assistance to the border population. The biggest challenges arise from the organization of the network, the population profile permeated by the characteristics of the border. As expectations, the differentiated view by government entities, investment in human, economic and structural resources, improvement in language skills, access to health services for the border population, and the creation of specific policies for health care in regions international border. It is expected to bring reflections and scientific information that favor more effective actions in management, assistance and care strategies by PHC professionals who work on international borders and other regions, as well as contributing to the improvement of the health-disease process, providing space and access for the care of the border population in the natural cycles of life, prevention, treatment and promotion of individual and collective health.